Medium and high temperature resistant nano ceramic coating, ceramic membrane and preparation method thereof

By using a combination of ceramic powders such as nanoalumina and binders such as silicon watersol, an all-inorganic nanoceramic coating was prepared, which solved the problem that it was difficult to prepare medium and high temperature-resistant ceramic films on the surface of titanium alloy, and achieved uniformity, density and good mechanical properties of the ceramic film.

CN119662058AActive Publication Date: 2025-03-21WUHAN UNIV OF TECH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411989211.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-21
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

It is difficult to prepare an all-inorganic ceramic film with medium and high temperature resistance and good mechanical properties on the surface of titanium alloys. The problems of traditional inorganic coatings such as low film formation, poor adhesion and prone to cracking cannot be effectively solved.

Method used

All-inorganic nanoceramic coatings composed of nanoalumina, nanoboronitride, glass powder, silicon water sol, nanomagnesium oxide, nanozirconia, mica powder, sepiol fiber and dispersant are used. After ball milling and stirring, step-by-step sintering and secondary coating processes of silicon water sol are carried out to form a dense ceramic coating.

Benefits of technology

It realizes the formation of a uniform, dense, medium and high temperature-resistant all-inorganic ceramic film on the surface of the titanium alloy, improves the film forming and adhesion properties of traditional inorganic coatings, avoids cracking problems, and takes into account better mechanical and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005223264990000011
    Figure HDA0005223264990000011
  • Figure HDA0005223264990000012
    Figure HDA0005223264990000012
  • Figure HDA0005223264990000021
    Figure HDA0005223264990000021
Patent Text Reader

Abstract

The invention discloses a medium and high temperature resistant and anti-corrosion nano ceramic coating which comprises the following main components in parts by weight: 20-30 parts of nano aluminum oxide, 10-15 parts of nano boron nitride, 10-15 parts of glass powder, 40-50 parts of silicon hydrosol, 1-2 parts of nano magnesium oxide, 1-2 parts of nano zirconium oxide, 1-2 parts of mica powder, 2-3 parts of borax, 0.5-2.0 parts of sepiolite fiber and 0.5-1 part of a dispersing agent. According to the invention, various ceramic powders are stably mixed in the silica sol, and the dispersing agent, the sepiolite fiber and the glass powder are introduced, so that the full-inorganic nano ceramic coating which is uniform, not easy to settle and good in film-forming property is formed; step-by-step sintering and a secondary coating process of silica sol are further combined, so that a compact ceramic coating is promoted to be obtained, and the problems that a traditional inorganic coating is poor in adhesive force, easy to crack and the like are effectively solved; the preparation method is simple, convenient to operate and suitable for popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic protective films, and specifically relates to a medium- and high-temperature resistant inorganic nano-ceramic coating, a ceramic film and a preparation method thereof. Background Art

[0002] With the rapid development of science and technology, the demand for energy is increasing day by day. Oil and gas exploration is gradually expanding to ultra-deep wells, high temperature and high pressure and highly corrosive environments, and involves a variety of unconventional oil and gas resources. In the process of high temperature, high pressure and highly corrosive oil and gas resource exploitation, oil pipes are often exposed to high concentrations of corrosive gases such as CO2, Cl2, H2S, etc. Some exploitation environments must also face the problem of corrosion in water. Such a harsh development environment makes most commonly used carbon alloy steel pipes and nickel alloy pipes unable to serve for a long time; higher requirements are put forward for the high corrosion resistance, high temperature resistance and high pressure resistance of oil pipes.

[0003] Titanium alloy has the advantages of high strength, low density, good corrosion resistance, low elastic modulus and high fatigue resistance, making it the preferred material in the oil pipe industry. However, titanium alloys exposed to high temperature and corrosive environments are still prone to problems such as stress corrosion and crevice corrosion, which can cause cracking, and still need to be treated with anti-corrosion on the surface. Covering the alloy surface with a high temperature resistant protective film can increase the service life of titanium alloy pipes in humid atmosphere and seawater media to cope with various pitting, acid corrosion and stress corrosion problems.

[0004] At present, the commercial protective film used on the surface of titanium alloy is mainly silicone coating. Although silicone coating is easy to form and easy to apply, it can generally only be used for a long time below 300°C. When the temperature is high, cracks are likely to form on the surface of the film layer, and the silicone component in the film layer will be carbonized and decomposed, resulting in continuous shedding of the film layer. If it is in a water vapor environment, titanium alloy is prone to corrosion. Although the preparation process of high-temperature resistant inorganic ceramic film (above 700°C) is relatively mature, it has poor adhesion and film-forming properties and cannot be used on the surface of titanium alloy. At present, the preparation process of corrosion-resistant ceramic films used in medium and high temperature areas is still blank, and some processes still cannot be separated from the use of silicone resins, cannot meet the service life requirements of the workpiece, and have limited mechanical properties; therefore, it is necessary to further develop all-inorganic ceramic films that are resistant to medium and high temperatures and can guarantee good mechanical properties, which has important research and application significance. Summary of the invention

[0005] The main purpose of the present invention is to provide a medium- and high-temperature resistant all-inorganic nano-ceramic coating in response to the problems and shortcomings of the prior art. The coating can form a ceramic film that evenly covers workpieces such as titanium alloys, and effectively solve the problems of low film-forming properties, poor adhesion, and easy cracking of traditional inorganic coatings.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A medium-high temperature resistant and anti-corrosion nano ceramic coating, the main components except a dispersing solvent and their weight proportions include: 20-30 parts of nano alumina, 10-15 parts of nano boron nitride, 10-15 parts of glass powder, 40-50 parts of silica hydrosol, 1-2 parts of nano magnesium oxide, 1-2 parts of nano zirconium oxide, 1-2 parts of mica powder, 2-3 parts of borax, 0.5-2.0 parts of sepiolite fiber and 0.5-1 part of a dispersant.

[0008] In the above scheme, the average particle size of the nano-aluminum oxide, nano-boron nitride, nano-magnesium oxide and nano-zirconium oxide is 20-50nm.

[0009] In the above scheme, the main components of the glass powder are silicon oxide and sodium oxide; its particle size is 15-25nm, and its melting point is 380-420℃.

[0010] In the above scheme, silica hydrosol is used as a slurry binder, and its silicon dioxide content is 38-42wt% and the average particle size is 8-15nm; the present invention uses silica hydrosol to bond nano-ceramic powder and mica powder to the surface of the titanium alloy pipe, and combines glass powder and a small amount of borax, which helps to bond various nano-ceramic particles and sepiolite fibers together to form a dense film layer during high-temperature sintering.

[0011] In the above scheme, the average particle size of the mica powder is 45-55 nm; the present invention utilizes the difference in particle size between nano-ceramic powder and mica powder to make the film layer on the surface of the titanium alloy more uniform and dense.

[0012] In the above scheme, the size of the sepiolite fiber is 50-200nm; the present invention utilizes the unique layered chain structure and good adsorption and rheological properties of the sepiolite fiber to make it easier for the film layer to extend on the titanium alloy surface, and after sintering, the film layer is uniform and dense and not easy to fall off.

[0013] In the above scheme, the dispersant is sodium tripolyphosphate.

[0014] In the above scheme, the dispersing solvent includes water, and the amount of water is 8-15 parts

[0015] Furthermore, the dispersion solvent also contains ethanol, and the content of ethanol is 35-45 parts.

[0016] The method for preparing the above-mentioned medium-high temperature resistant and anti-corrosion nano-ceramic coating comprises the following steps:

[0017] 1) adding weighed nano-alumina, nano-boron nitride, nano-magnesium oxide, nano-zirconium oxide, glass powder, dispersant, borax, sepiolite fiber and mica powder and ball milling to obtain a composite powder;

[0018] 2) Adding silica hydrosol to the obtained composite powder, and then adding a dispersing solvent, stirring evenly to obtain a nano ceramic coating that is resistant to medium and high temperatures and anti-corrosion.

[0019] The present invention also provides a method for preparing a medium-high temperature resistant and anti-corrosion nano-ceramic film, comprising the following steps:

[0020] 1) Clean and roughen the surface of the workpiece;

[0021] 2) applying a medium-high temperature resistant and anti-corrosion nano-ceramic coating on the surface of the workpiece treated in step 1), and drying naturally to form a film;

[0022] 3) Perform a primary heat treatment, cool it, and then coat the surface with silica hydrosol and perform a secondary heat treatment, so as to form the medium-high temperature and corrosion-resistant nano-ceramic film on the surface of the workpiece.

[0023] In the above solution, the workpiece is a titanium alloy workpiece or a tungsten alloy workpiece, etc.

[0024] In the above scheme, the cleaning step includes steps such as acetone degreasing, hydrochloric acid pickling and water washing.

[0025] In the above scheme, the roughening treatment uses 100-mesh sandpaper.

[0026] In the above scheme, the temperature used in the primary heat treatment is 500-700°C, the heating rate is 2-4°C / min, and the insulation time is 3-5h; the temperature used in the secondary heat treatment is 500-700°C, the heating rate is 2-4°C / min, and the insulation time is 1-3h.

[0027] The present invention stably mixes ceramic powder in silica sol and adds a dispersant to make a slurry. The ceramic powder is bonded together by utilizing the silica sol's strong bonding force and resistance to medium and high temperatures (350-800°C). The ceramic powder is then sintered in steps and combined with a secondary coating process of silica sol to obtain a densified ceramic coating.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1) The present invention stably mixes a variety of ceramic powders such as nano-alumina, nano-boron nitride, nano-magnesium oxide and nano-zirconium oxide in silica sol, and introduces a dispersant, sepiolite fiber, mica powder and glass powder to make a slurry to form a uniform, non-settling and well-film-forming all-inorganic nano-ceramic coating that is resistant to medium and high temperatures;

[0030] 2) The present invention further combines the step-by-step sintering process with the secondary coating technology of silica sol to promote the acquisition of a dense ceramic coating, while taking into account the properties of good adhesion and crack resistance;

[0031] 3) The nano-ceramic coating obtained by the present invention has good film-forming and adhesion properties, and can effectively improve the problems of low film-forming, poor adhesion, easy cracking, etc. of traditional inorganic coatings; and the preparation method involved is relatively simple, easy to operate, and has wide applicability. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is the XRD pattern of the ceramic membrane obtained in Example 1;

[0033] Figure 2 This is a SEM image of the ceramic membrane obtained in Example 1;

[0034] Figure 3 This is a SEM image of the ceramic membrane obtained in Example 1 after high temperature resistance test;

[0035] Figure 4 This is a surface morphology of the ceramic membrane obtained in Example 1 after high temperature treatment;

[0036] Figure 5 This is a photo of the ceramic membrane obtained in Example 1 after being treated in a water bath at 80°C;

[0037] Figure 6 The ceramic membrane obtained in Example 1 is photographed before and after being subjected to hydrothermal treatment and then hydrothermally treated at 200°C;

[0038] Figure 7 These are photos of the titanium alloy sample coated with ceramic coating on the surface in Example 1 before and after the acid resistance test;

[0039] Figure 8 These are photos of the titanium alloy sample coated with ceramic coating on the surface in Example 1 before and after the alkali resistance test;

[0040] Fig. 9 These are photos of the titanium alloy sample coated with ceramic coating on the surface in Example 1 before and after the salt resistance test;

[0041] Fig.10 This is the SEM image of the ceramic membrane obtained in Comparative Example 1;

[0042] Fig.11 This is a SEM image of the ceramic membrane obtained in Example 2;

[0043] Fig.12 This is the SEM image of the ceramic membrane obtained in Example 3. DETAILED DESCRIPTION

[0044] In order to more clearly and thoroughly illustrate the advantages of the present invention, the present invention is further described in detail through the following specific implementation cases and accompanying drawings. The specific embodiments described herein are only used to illustrate the present invention and are not used to limit the scope of protection of the present invention. After reading the present invention, the various equivalent forms of modifications to the present invention by those skilled in the art are all within the scope of the claims attached to this application.

[0045] In the following examples, the average particle size of the nano-aluminum oxide used is 30 nm; the average particle size of the nano-boron nitride is 50 nm; the average particle size of the nano-magnesium oxide is 30 nm; and the average particle size of the nano-zirconium oxide is 20 nm.

[0046] The glass powder used is commercially available glass powder, the main components of which are silicon oxide and sodium oxide; the average particle size thereof is 20 nm, and the melting point thereof is about 400°.

[0047] The silica hydrosol used has a silicon oxide content of 40 wt % and an average particle size of 10 nm.

[0048] The sepiolite fibers used are commercially available sepiolite fibers with a size of 50-200 nm.

[0049] The dispersant used is sodium tripolyphosphate.

[0050] Example 1

[0051] A medium-high temperature resistant all-inorganic nano-ceramic coating and film layer, the preparation method of which comprises the following steps:

[0052] The nano ceramic coating:

[0053] 1) Weigh the raw materials of the ceramic slurry according to the proportion, and the raw materials and their weight proportions include: 20 parts of nano-alumina, 10 parts of nano-boron nitride, 10 parts of glass powder, 40 parts of silica hydrosol, 1 part of nano-magnesium oxide, 1 part of nano-zirconium oxide, 1 part of mica powder, 2 parts of borax, 0.5 parts of sodium tripolyphosphate, and 1.0 parts of sepiolite fiber;

[0054] 2) adding weighed nano-ceramic powders (nano-alumina, nano-boron nitride, nano-magnesium oxide, nano-zirconium oxide; the same below), glass powder, dispersant, borax, sepiolite fiber and mica powder into a ball mill, mixing and grinding thoroughly, wherein the abrasive is ZrO2 ball, the ball-to-material ratio is 5:1, grinding at a speed of 300 rpm for 5 hours, and adding a small amount of ethanol as a grinding aid;

[0055] 3) Add silica hydrosol to the ground composite powder, and add 10 parts of deionized water and 40 parts of ethanol in small amounts and multiple times, and stir thoroughly to obtain a uniform, non-settling, medium- and high-temperature resistant all-inorganic nano-ceramic coating.

[0056] All-inorganic nano-ceramic film layer resistant to medium and high temperatures:

[0057] (1) The surface of the titanium alloy workpiece should be degreased with acetone, pickled with hydrochloric acid, washed with water, and roughened with sandpaper (using 100-grit sandpaper);

[0058] (2) applying the obtained medium-high temperature resistant all-inorganic nano-ceramic coating evenly on the surface of the workpiece by manual brushing, and then placing it in a clean environment to allow it to dry naturally to form a film;

[0059] (3) Place the workpiece in a methane fluorine furnace and heat it to 700°C at a rate of 2°C / min and keep it warm for 3 hours; take out the workpiece after the heat treatment, cool it to room temperature, and then evenly brush a layer of silica hydrosol on its surface to completely cover the surface defects after the first film formation. After the surface is dry, place it in a tubular furnace for a second heat treatment. The specific steps are to heat it to 700°C at a rate of 2°C / min and keep it warm for 1 hour, so as to avoid the workpiece being attached with a medium- and high-temperature resistant and anti-corrosion nano-ceramic film.

[0060] The obtained workpiece samples were subjected to high temperature resistance, salt resistance, alkali resistance, acid resistance, room temperature water resistance and hydrothermal tests. The specific steps and test results are as follows:

[0061] High temperature resistance experiment: Place the sample in a Muffle furnace for heat treatment at 800℃, with a heating rate of 2℃ / min and a holding time of 2h.

[0062] Salt resistance test: Soak the sample in 3.5% NaCl solution for fifteen days, and observe whether there is any obvious change on the surface of the sample and whether it will fall off.

[0063] Alkali resistance test: The sample is immersed in 3.5% NaOH solution for fifteen days, and the surface of the sample is observed for obvious changes and shedding.

[0064] Acid resistance test: After dropping 3.5% HCl solution on the sample for 12 hours, observe whether there is any obvious change or shedding on the sample surface.

[0065] Room temperature water resistance test: Place the sample in a beaker and transfer it to an 80°C water bath. After 3 days, observe the state of the sample surface film.

[0066] Hydrothermal experiment: Place the sample in a hydrothermal kettle, add deionized water, seal it and place it in a muffle furnace. Set the temperature to 200°C, take it out after 12 hours, and observe the state of the film layer on the sample surface.

[0067] Figure 1 It can be seen that the main phase components of the ceramic membrane are Al2O3, ZrO2 and MgO. Figure 2It can be seen that the formed ceramic film layer is very dense, nano ceramic particles are dispersed between the film layers, and the length of the sepiolite fiber is more than 5μm and is also embedded in the ceramic film. The hardness of the obtained ceramic film is 5H when tested by a hardness tester.

[0068] Figure 3 It can be seen from the scanning electron microscope image that the morphology of the ceramic membrane does not change much after heat treatment at 800℃, indicating that the membrane has good resistance to medium and high temperatures. Figure 4 This is a photo of the film layer after high temperature resistance. It can be seen that the coating has not changed much. Figure 5 and Figure 6 It shows that the ceramic membrane is relatively dense and has certain water resistance. Figure 7 , Figure 8 and Fig. 9 It shows that the surface of the ceramic membrane has no significant changes after alkali resistance, acid resistance and salt resistance tests.

[0069] Comparative Example 1

[0070] A medium-high temperature resistant all-inorganic nano-ceramic coating and film layer, the preparation method of which comprises the following steps:

[0071] The nano ceramic coating:

[0072] 1) Weigh the raw materials of the ceramic slurry according to the proportion, and the raw materials and their weight proportions include: 20 parts of nano-alumina, 10 parts of nano-boron nitride, 10 parts of glass powder, 40 parts of silica hydrosol, 1 part of nano-magnesium oxide, 1 part of nano-zirconium oxide, 1 part of mica powder, 2 parts of borax, and 0.5 parts of sodium tripolyphosphate dispersant;

[0073] 2) adding the weighed nano-ceramic powder, glass powder, dispersant, borax and mica powder into a ball mill, mixing and grinding them thoroughly, wherein the abrasive is ZrO2 ball, the ball-to-material ratio is 5:1, grinding at a speed of 300 rpm for 5 hours, and adding a small amount of ethanol as a grinding aid;

[0074] 3) Add silica hydrosol to the ground composite powder, and add 10 parts of deionized water and 40 parts of ethanol in small amounts and multiple times, and stir thoroughly to obtain a uniform, non-settling, medium- and high-temperature resistant all-inorganic nano-ceramic coating.

[0075] All-inorganic nano-ceramic film layer resistant to medium and high temperatures:

[0076] (1) The surface of the titanium alloy workpiece should be degreased with acetone, pickled with hydrochloric acid, washed with water, and roughened with sandpaper (using 100-grit sandpaper);

[0077] (2) applying the obtained medium-high temperature resistant all-inorganic nano-ceramic coating evenly on the surface of the workpiece by manual brushing, and then placing it in a clean environment to allow it to dry naturally to form a film;

[0078] (3) Place the workpiece in a muffle furnace and heat it to 700°C at a rate of 2°C / min and keep it warm for 3 hours; take out the workpiece after heat treatment, cool it to room temperature, and then evenly brush silica hydrosol on its surface. After the surface is dry, place it in a tubular furnace for a second heat treatment. The specific steps are: heat it to 700°C at a rate of 2°C / min and keep it warm for 1 hour, so as to avoid the workpiece being attached with a medium- and high-temperature resistant and anti-corrosion nano-ceramic film.

[0079] Fig.10 It can be seen that the ceramic membrane without sepiolite fiber is composed of ceramic membrane layer and ceramic particles. The sintered membrane layer is easy to crack and has low strength, which does not meet the requirements.

[0080] Example 2

[0081] A medium-high temperature resistant all-inorganic nano-ceramic coating and film layer, the preparation method of which comprises the following steps:

[0082] The nano ceramic coating:

[0083] 1) Weigh the raw materials of ceramic slurry according to the proportion, and the raw materials and their weight proportions include: 20 parts of nano-alumina, 10 parts of nano-boron nitride, 10 parts of glass powder, 40 parts of silica hydrosol, 1 part of nano-magnesium oxide, 1 part of nano-zirconium oxide, 1 part of mica powder, 2 parts of borax, 0.5 parts of sodium tripolyphosphate dispersant, and 0.5 parts of sepiolite fiber;

[0084] 2) adding the weighed nano-ceramic powder, glass powder, dispersant, borax, sepiolite fiber and mica powder into a ball mill, mixing and grinding them thoroughly, wherein the abrasive is ZrO2 ball, the ball-to-material ratio is 5:1, grinding at a speed of 300 rpm for 5 hours, and adding a small amount of ethanol as a grinding aid;

[0085] 3) Add silica hydrosol to the ground composite powder, and add 10 parts of deionized water and 40 parts of ethanol in small amounts and multiple times, and stir thoroughly to obtain a uniform, non-settling, medium- and high-temperature resistant all-inorganic nano-ceramic coating.

[0086] All-inorganic nano-ceramic film layer resistant to medium and high temperatures:

[0087] (1) The surface of the titanium alloy workpiece should be degreased with acetone, pickled with hydrochloric acid, washed with water, and roughened with sandpaper (using 100-grit sandpaper);

[0088] (2) applying the obtained medium-high temperature resistant all-inorganic nano-ceramic coating evenly on the surface of the workpiece by manual brushing, and then placing it in a clean environment to allow it to dry naturally to form a film;

[0089] (3) Place the workpiece in a muffle furnace and heat it to 700°C at a rate of 2°C / min and keep it warm for 3 hours; take out the workpiece after the heat treatment, cool it to room temperature, and then evenly brush a layer of silica hydrosol on its surface. After the surface is dry, place it in a tubular furnace for a second heat treatment. The specific steps are to heat it to 700°C at a rate of 2°C / min and keep it warm for 1 hour, so as to avoid the workpiece being attached with a medium- and high-temperature resistant and anti-corrosion nano-ceramic film.

[0090] Fig.11 It can be seen that the ceramic membrane with 0.5 parts of sepiolite fiber added is assembled by ceramic particles.

[0091] Example 3

[0092] A medium-high temperature resistant all-inorganic nano-ceramic coating and film layer, the preparation method of which comprises the following steps:

[0093] The nano ceramic coating:

[0094] 1) Weigh the raw materials of the ceramic slurry according to the proportion, and the raw materials and their weight proportions include: 20 parts of nano-alumina, 10 parts of nano-boron nitride, 10 parts of glass powder, 40 parts of silica hydrosol, 1 part of nano-magnesium oxide, 1 part of nano-zirconium oxide, 1 part of mica powder, 2 parts of borax, 0.5 parts of sodium tripolyphosphate dispersant, and 1.5 parts of sepiolite fiber;

[0095] 2) adding the weighed nano-ceramic powder, glass powder, dispersant, borax and mica powder into a ball mill, mixing and grinding them thoroughly, wherein the abrasive is ZrO2 ball, the ball-to-material ratio is 5:1, grinding at a speed of 300 rpm for 5 hours, and adding a small amount of ethanol as a grinding aid;

[0096] 3) Add silica hydrosol to the ground composite powder, and add 10 parts of deionized water and 40 parts of ethanol in small amounts and multiple times, and stir thoroughly to obtain a uniform, non-settling, medium- and high-temperature resistant all-inorganic nano-ceramic coating.

[0097] All-inorganic nano-ceramic film layer resistant to medium and high temperatures:

[0098] (1) The surface of the titanium alloy workpiece should be degreased with acetone, pickled with hydrochloric acid, washed with water, and roughened with sandpaper (using 100-grit sandpaper);

[0099] (2) applying the obtained medium-high temperature resistant all-inorganic nano-ceramic coating evenly on the surface of the workpiece by manual brushing, and then placing it in a clean environment to allow it to dry naturally to form a film;

[0100] (3) placing the workpiece in a muffle furnace and heating it to 700°C at a rate of 2°C / min and keeping it warm for 3 hours; taking out the workpiece after the heat treatment, cooling it to room temperature, and then evenly brushing a layer of silica hydrosol on its surface. After the surface is dry, placing it in a tubular furnace for a second heat treatment. The specific steps are: heating it to 700°C at a rate of 2°C / min and keeping it warm for 1 hour, so as to avoid the workpiece being attached with a medium- and high-temperature resistant and anti-corrosion nano-ceramic film.

[0101] Fig.12 It can be seen that in the ceramic membrane with 1.5 parts of sepiolite fiber added, the sepiolite fibers are gathered on the surface of the membrane layer, some of them are combined with the nano-ceramic particles, and some of them are not easy to disperse evenly.

[0102] Example 4

[0103] A medium-high temperature resistant all-inorganic nano-ceramic coating and film layer, the preparation method of which comprises the following steps:

[0104] The nano ceramic coating:

[0105] 1) Weigh the raw materials of the ceramic slurry according to the proportion, and the raw materials and their weight proportions include: 20 parts of nano-alumina, 10 parts of nano-boron nitride, 10 parts of glass powder, 40 parts of silica hydrosol, 1 part of nano-magnesium oxide, 1 part of nano-zirconium oxide, 1 part of mica powder, 2 parts of borax, 0.5 parts of sodium tripolyphosphate dispersant, and 1.0 parts of sepiolite fiber;

[0106] 2) adding the weighed nano-ceramic powder, glass powder, dispersant, borax, sepiolite fiber and mica powder into a ball mill, mixing and grinding them thoroughly, wherein the abrasive is ZrO2 ball, the ball-to-material ratio is 5:1, grinding at a speed of 300 rpm for 5 hours, and adding a small amount of ethanol as a grinding aid;

[0107] 3) Add silica hydrosol to the ground composite powder, and add 10 parts of deionized water and 40 parts of ethanol in small amounts and multiple times, and stir thoroughly to obtain a uniform, non-settling, medium- and high-temperature resistant all-inorganic nano-ceramic coating.

[0108] All-inorganic nano-ceramic film layer resistant to medium and high temperatures:

[0109] (1) The surface of the titanium alloy workpiece should be degreased with acetone, pickled with hydrochloric acid, washed with water, and roughened with sandpaper (using 100-grit sandpaper);

[0110] (2) applying the obtained medium-high temperature resistant all-inorganic nano-ceramic coating evenly on the surface of the workpiece by manual brushing, and then placing it in a clean environment to allow it to dry naturally to form a film;

[0111] (3) Place the workpiece in a muffle furnace and heat it to 600°C at a rate of 2°C / min and keep it warm for 3 hours; take out the workpiece after the heat treatment, cool it to room temperature, and then evenly brush a layer of silica hydrosol on its surface. After the surface is dry, place it in a tubular furnace for a second heat treatment. The specific steps are to heat it to 600°C at a rate of 2°C / min and keep it warm for 1 hour, so as to avoid the workpiece being attached with a medium- and high-temperature resistant and anti-corrosion nano-ceramic film.

[0112] Example 5

[0113] A medium-high temperature resistant all-inorganic nano-ceramic coating and film layer, the preparation method of which comprises the following steps:

[0114] The nano ceramic coating:

[0115] 1) Weigh the raw materials of the ceramic slurry according to the proportion, and the raw materials and their weight proportions include: 25 parts of nano-alumina, 13 parts of nano-boron nitride, 12 parts of glass powder, 45 parts of silica hydrosol, 2 parts of nano-magnesium oxide, 2 parts of nano-zirconium oxide, 2 parts of mica powder, 3 parts of borax, 1 part of sodium tripolyphosphate dispersant, and 1 part of sepiolite fiber;

[0116] 2) adding the weighed nano-ceramic powder, glass powder, dispersant, borax, sepiolite fiber and mica powder into a ball mill, mixing and grinding them thoroughly, wherein the abrasive is ZrO2 ball, the ball-to-material ratio is 5:1, grinding at a speed of 300 rpm for 5 hours, and adding a small amount of ethanol as a grinding aid;

[0117] 3) Add silica hydrosol to the ground composite powder, and add 10 parts of deionized water and 40 parts of ethanol in small amounts and multiple times, and stir thoroughly to obtain a uniform, non-settling, medium- and high-temperature resistant all-inorganic nano-ceramic coating.

[0118] All-inorganic nano-ceramic film layer resistant to medium and high temperatures:

[0119] (1) The surface of the titanium alloy workpiece should be degreased with acetone, pickled with hydrochloric acid, washed with water, and roughened with sandpaper (using 100-grit sandpaper);

[0120] (2) applying the obtained medium-high temperature resistant all-inorganic nano-ceramic coating evenly on the surface of the workpiece by manual brushing, and then placing it in a clean environment to allow it to dry naturally to form a film;

[0121] (3) Place the workpiece in a muffle furnace and heat it to 800°C at a rate of 2°C / min and keep it warm for 3 hours; take out the workpiece after the heat treatment, cool it to room temperature, and then evenly brush a layer of silica hydrosol on its surface. After the surface is dry, place it in a tubular furnace for a second heat treatment. The specific steps are to heat it to 800°C at a rate of 2°C / min and keep it warm for 1 hour, so as to avoid the workpiece being attached with a medium- and high-temperature resistant and anti-corrosion nano-ceramic film.

[0122] Comparative Example 2

[0123] A medium-high temperature resistant all-inorganic nano-ceramic coating and film layer, the preparation method of which comprises the following steps:

[0124] The nano ceramic coating:

[0125] 1) Weigh the raw materials of ceramic slurry according to the proportion, and the raw materials and their weight proportions include: 20 parts of nano-alumina, 10 parts of nano-boron nitride, 10 parts of glass powder, 40 parts of silica hydrosol, 1 part of nano-magnesium oxide, 1 part of nano-zirconium oxide, 1 part of mica powder, 2 parts of borax, 0.5 parts of sodium tripolyphosphate dispersant, and 1.0 parts of sepiolite fiber.

[0126] 2) adding the weighed nano-ceramic powder, glass powder, dispersant, borax and mica powder into a ball mill, mixing and grinding them thoroughly, wherein the abrasive is ZrO2 ball, the ball-to-material ratio is 5:1, grinding at a speed of 300 rpm for 5 hours, and adding a small amount of ethanol as a grinding aid;

[0127] 3) Add silica hydrosol to the ground composite powder, and add 10 parts of deionized water and 40 parts of ethanol in small amounts and multiple times, and stir thoroughly to obtain a uniform, non-settling, medium- and high-temperature resistant all-inorganic nano-ceramic coating.

[0128] All-inorganic nano-ceramic film layer resistant to medium and high temperatures:

[0129] (1) The surface of the titanium alloy workpiece should be degreased with acetone, pickled with hydrochloric acid, washed with water, and roughened with sandpaper (using 100-grit sandpaper);

[0130] (2) applying the obtained medium-high temperature resistant all-inorganic nano-ceramic coating evenly on the surface of the workpiece by manual brushing, and then placing it in a clean environment to allow it to dry naturally to form a film;

[0131] (3) Place the tube in a Muffle furnace and heat it to 700°C at a rate of 2°C / min and keep it at that temperature for 3 h.

[0132] After testing, it was found that the obtained film layer had defects on its surface, and its corresponding performance in terms of resistance to medium and high temperatures and corrosion resistance was poor.

[0133] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A medium-high temperature resistant and anti-corrosion nano-ceramic coating, characterized in that: The main components except the dispersing solvent and their weight proportions include: 20-30 parts of nano-alumina, 10-15 parts of nano-boron nitride, 10-15 parts of glass powder, 40-50 parts of silica hydrosol, 1-2 parts of nano-magnesium oxide, 1-2 parts of nano-zirconium oxide, 1-2 parts of mica powder, 2-3 parts of borax, 0.5-2.0 parts of sepiolite fiber and 0.5-1 part of dispersant.

2. The nano ceramic coating according to claim 1, characterized in that: The average particle size of the nano-aluminum oxide, nano-boron nitride, nano-magnesium oxide and nano-zirconium oxide is 20-50 nm.

3. The nano ceramic coating according to claim 1, characterized in that: The main components of the glass powder are silicon oxide and sodium oxide; its particle size is 15-25nm and its melting point is 380-420℃.

4. The nano ceramic coating according to claim 1, characterized in that: In the silica hydrosol, the content of silicon dioxide is 38-42 wt % and the average particle size is 8-15 nm.

5. The nano ceramic coating according to claim 1, characterized in that: The average particle size of the mica powder is 45-55nm; the size of the sepiolite fiber is 50-200nm.

6. The nano ceramic coating according to claim 1, characterized in that: The dispersant is sodium tripolyphosphate.

7. The nano ceramic coating according to claim 1, characterized in that: The dispersing solvent comprises water, and the amount of water used is 8-15 parts.

8. The method for preparing the medium-high temperature and high temperature corrosion resistant nano ceramic coating according to any one of claims 1 to 7, characterized in that: The steps include: 1) adding weighed nano-alumina, nano-boron nitride, nano-magnesium oxide, nano-zirconium oxide, glass powder, dispersant, borax, sepiolite fiber and mica powder to perform ball milling to obtain a composite powder; 2) Adding silica hydrosol to the obtained composite powder, and then adding a dispersing solvent, stirring evenly to obtain a nano ceramic coating that is resistant to medium and high temperatures and anti-corrosion.

9. A method for preparing a nano-ceramic film using the medium-high temperature and anti-corrosion nano-ceramic coating according to any one of claims 1 to 7, characterized in that: The steps include: 1) Clean and roughen the surface of the workpiece; 2) applying a medium-high temperature resistant and anti-corrosion nano-ceramic coating on the surface of the workpiece treated in step 1), and drying naturally to form a film; 3) Perform a primary heat treatment, cool it, and then coat the surface with silica hydrosol and perform a secondary heat treatment, so as to form the medium-high temperature and corrosion-resistant nano-ceramic film on the surface of the workpiece.

10. The method according to claim 9, characterized in that The temperature used in the primary heat treatment is 500-700°C, the heating rate is 2-4°C / min, and the insulation time is 3-5h; the temperature used in the secondary heat treatment is 500-700°C, the heating rate is 2-4°C / min, and the insulation time is 1-3h.

Citation Information

Patent Citations

  • Water-based inorganic coating and preparation method thereof

    CN114085557A

  • Silicate compound

    CN1146191A

  • Inorganic high-temperature ceramic coating as well as preparation method and application thereof

    CN115403944A

  • Paint for prepn. of aluminium oxide ceramic coating layer and its coating method

    CN1259547A

  • Acid resistant high temperature coating

    EP1900782A1